Binding of Plasmodium falciparum-infected erythrocytes to the membrane-bound form of Fractalkine/CX(3)CL1 - Hatabu, Toshimitsu (National Academy of Sciences, 2003)
Plasmodium falciparum-infected erythrocytes (pRBCs) adhere to the endothelium via receptors expressed on the surface of vascular endothelial cells (EC) and sequester in the microvasculature of several organs and block the blood circulation. The sequestration, which involves receptors, may be related to the severity of malaria. Here, we report that pRBCs bind to the membrane-bound form of Fractalkine/CX(3)CL1 (FKN), which is expressed on the surface of vascular EC in various organs. pRBCs adhered to FKN on the surface of FKN cDNA-transfected Chinese hamster ovary cells (CHO-FKN cells). Both the recombinant human FKN-chemokine domain (FKN-CD) and anti-FKN-CD antibody efficiently blocked adherence of pRBCs to CHO-FKN cells. Similar to binding between FKN and FKN receptor on blood mononuclear cells, two amino acid residues, Lys-7 and Arg-47 within FKN-CD, were critical for FKN-pRBC binding. Immunohistological analysis revealed the expression of FKN on EC at the site of sequestration in the brain of a patient with cerebral malaria. These results suggest that the membrane-bound form of FKN acts as a receptor for pRBCs, and this may contribute to furthering our present understanding of cytoadherence in the pathology of falciparum malaria.